A new normal with cataract surgery during COVID-19 pandemic - Jagadesh C Reddy; Pravin K Vaddavalli; Namrata Sharma; Mahipal S Sachdev; Y L Rajashekar; Rajesh Sinha; Amar Agarwal; Amit Porwal; Arup Chakrabarti; Barun Kumar Nayak; Bhudhendra Kumar Jain; D Chandrasekhar; et al. (Indian Journal of Ophthalmology, 2020)
Cataract is the second leading cause of preventable blindness on the globe. Several programs across the country have been running efficiently to increase the cataract surgical rates and decrease blindness due to cataract. The current COVID-19 pandemic has led to a complete halt of these programs and thus accumulating all the elective cataract procedures. At present with the better understanding of the safety precautions among the health care workers and general population the Government of India (GoI) has given clearance for functioning of eye care facilities. In order to facilitate smooth functioning of every clinic, in this paper, we prepared preferred practice pattern based on consensus discussions between leading ophthalmologists in India including representatives from major governmental and private institutions as well as the All India Ophthalmological Society leadership. These guidelines will be applicable to all practice settings including tertiary institutions, corporate and group practices and individual eye clinics. The guidelines include triage, use of personal protective equipment, precautions to be taken in the OPD and operating room as well for elective cataract screening and surgery. These guidelines have been prepared based on current situation but are expected to evolve over a period of time based on the ongoing pandemic and guidelines from GoI.